Impact of carbon to nitrogen ratio on nitrogen removal at a low oxygen concentration in a sequencing batch biofilm reactor. - Tan, Chong (Water Science and Technology)
A sequencing batch biofilm reactor (SBBR) filled with polyurethane (PU) was operated in low dissolved oxygen (DO) (0.1?0.9 mg/L) at three different carbon to nitrogen ratios (C/N ratios) (C/N = 1.8:1, 5.0:1 and 10.5:1) with focus on reactor performance and microbial community composition of nitrifying and denitrifying bacteria. Meanwhile, the ammonium, nitrite, nitrate, pH and dissolved oxygen were analyzed to monitor the process of nitrification-denitrification. The reactor had a steady ammonium removal in spite of a large variation in the initial ammonium loading (the ammonium removal efficiency was 87.2% at C/N 1.8:1, 92.9% at C/N 5.0:1, 88.4% at C/N 10.5:1). However, the total nitrogen (TN) removal was strongly affected by the initial organic loading (the TN removal efficiency was 55.2% at C/N 1.8:1, 74.3% at C/N 5.0:1, 79.0% at C/N 10.5:1). It was indicated that higher organic load promoted denitrification. The real-time quantitative polymerase chain reaction (real-time qPCR) analysis shown that Beta-proteobacteria occupied over 35% numerically. As for the Nitrosomonas sp., Nitrosospira sp. and Nitrospira sp. gene copy numbers, their abundance was generally in the order of magnitude of 1010. The Nitrosospira sp. fluctuated significantly in the range of 3.1?9.8% at different C/N ratios, while the Nitrosomonas sp. just changed a little.